Analysis of Factors of High-tech Industries Growth: A Case Study of the Late USSR - D. V. Didenko; N. V. Grineva (Мир новой экономики)
Explanation of the role high-tech industries play in ensuring sustainable economic growth is significant in the contemporary environment. Also, it is relevant in theoretical discourses of modernization, neo-industrialization, and industrial policy that are similar in their structure. The purpose of the study is to assess the factors of dynamics of the most high-tech industries and the entire Soviet industry when having faced economic growth slowdown, with emphasis on institutional and technological components. The key hypothesis is that in the high-tech industries in the 1960s and 1980s, the institutional environment appeared to be a more significant factor than the technological level. The variety of the sources utilized includes calculations and estimates from the research literature and selected indicators from the official statistics. The econometric analysis of the data is based on an exogenous growth model in the form of the Cobb- Douglas production function, augmented with human capital in Mankiw, Romer, Weil (1992), modified in Didenko, Grineva (2020) by introducing variables that proxy for institutional and general technological dynamics. In this paper, we test it using lagged variables in per capita and rate-of-change terms. The marginal rate of technical substitution of physical by human capital, measured in such a way and indicating the flexibility of management of factors of production, exposed a stable level both in the entire industry of the USSR and its high-tech branches. At the same time, our key hypothesis found weak support.